Using Eye Movements to Investigate Word Frequency Effects in Children's Sentence Reading - Joseph, H; Nation, K; Liversedge, S (2013)
Although eye movements have been used widely to investigate how skilled adult readers process written language, relatively little research has used this methodology with children. This is unfortunate as, as we discuss here, eye-movement studies have significant potential to inform our understanding of children's reading development. We consider some of the empirical and theoretical issues that arise when using this methodology with children, illustrating our points with data from an experiment examining word frequency effects in 8-yearold children's sentence reading. Children showed significantly longer gaze durations to low- than high-frequency words, demonstrating that linguistic characteristics of text drive children's eye movements as they read. We discuss these findings within the broader context of how eye-movement studies can inform our understanding of children's reading, and can assist with the development of appropriately targeted interventions to support children as they learn to read. Copyright 2013 by the National Association of School Psychologists, ISSN 0279-6015.